Lessons learned from the Alberta Border Testing Pilot Program - Kersen, Jaling; Scory, Tayler D.; Akeju, Oluwasefunmi; Weaver, Robert G.; Barnieh, Lianne; Ronksley, Paul E.; Leal, Jenine; Blue, Dean; O’Neill, Erin; Campbell, David J. T.; Tonelli, Marcello; Lunney, Meaghan (Frontiers in Health Services, 2023)
Background During the Coronavirus disease (COVID-19) pandemic, countries implemented border control and quarantine measures to reduce transmission. The Alberta Border Testing Pilot Program (ABTPP) allowed international travellers entering Alberta to reduce their quarantine period following two negative COVID-19 tests. We evaluated participant experiences with the ABTPP and implementation. Method We used a parallel convergent mixed-methods design to explore participant experiences through electronic web-based questionnaires (n = 21,089; n = 13,839) and semi-structured telephone interviews (n = 30). We evaluated implementation through three staff focus groups (n = 11). We analysed questionnaires using descriptive statistics and analysed interviews using inductive and deductive thematic analysis. We deductively coded focus group data using the 2009 Consolidated Framework for Implementation Research (CFIR). Results Questionnaires indicated minimal issues with registration forms (91.7%), symptom reports (95.5%), and COVID-19 testing (95.7%). Most respondents (95.1%) expressed willingness to participate in the ABTPP again. Interviews revealed three themes related to participant experience: program efficiency, clarity of information, and requisite effort. Focus groups identified key implementation facilitators including the single health information system, strong stakeholder partnerships, and good communication across partnerships. Barriers included program complexity, implementation timeline, and evolving external context. Discussion Participants reported high satisfaction with the ABTPP. Border testing programs should have high efficiency, require low effort, and use messaging that is clear and consistent. The effective implementation of border testing programs may be facilitated by strong leadership, adaptability, automated components, good communication, and simple technology. Learnings from participants and staff may help improve the implementation of border control programs for future pandemics or other emergencies. Conclusions The ABTTP was a novel border control measure during the COVID-19 pandemic. Our evaluation of both participant and staff experiences demonstrated high levels of traveller satisfaction and identified areas for improvement that can inform the development of future border control measures.